Identifikasi Keragaman Penyediaan Sarana Prasarana pada Perumahan Peri-Urban Kabupaten Sleman - Sekar Ari Utari; Ardhya Nareswari (ATRIUM: Jurnal Arsitektur, 2021)
Title: Diversity Identification of Infrastructure Provision in Peri-Urban Housing Sleman Regency The procurement of housing infrastructure has been regulated through SNI 03-1733-2004. However, in the field, developers have their own considerations and creativity in providing them. The diversity of provision raises the problem of equal public access to infrastructure. This study aims to identify the diversity of housing infrastructure provision in Sleman Regency. The research used deductive-qualitative method. The analysis was carried out through the stages of data grouping, housing type analysis, analysis of infrastructure availability and comparative analysis. The results showed different provision between small-scale and medium-scale housing. Basic infrastructure is the top priority and security infrastructure is the second priority. Variations are found in amenities and health facilities and the least provided are religious and educational facilities.